A New Decision Model Approach for Health Technology Assessment and a Case Study for Dialysis Alternatives in Turkey - VAYVAY, ÖZALP (MDPI, 2020)
Background: This paper presents a generic Multi-Criteria Decision Analysis (MCDA) model for Health Technology Assessment (HTA) decision-making, which can be applied to a wide range of HTA studies, regardless of the healthcare technology type under consideration. Methods: The HTA Core Model((R)) of EUnetHTA was chosen as a basis for the development of the MCDA model because of its common acceptance among European Union countries. Validation of MCDA4HTA was carried out by an application with the HTA study group of the Turkish Ministry of Health. The commitment of the decision-making group is completed via an online application of 10 different questionnaires. The Analytic Hierarchy Process (AHP) is used to determine the weights. Scores of the criteria in MCDA4HTA are gathered directly from the HTA report. The performance matrix in this application is run with fuzzy Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), fuzzy Vise Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR), and goal programming MCDA techniques. Results: Results for fuzzy VIKOR, fuzzy TOPSIS, and goal programming are 0.018, 0.309, and 0.191 for peritoneal dialysis and 0.978, 0.677, and 0.327 for hemodialysis, respectively. Conclusions: Peritoneal dialysis is found to be the best choice under the given circumstances, despite its higher costs to society. As an integrated decision-making model for HTA, MCDA4HTA supports both evidence-based decision policy and the transparent commitment of multi-disciplinary stakeholders.
Keywords: HTA; decision-making; MCDA; AHP; TOPSIS; VIKOR; goal programming; fuzzy; ANALYTIC HIERARCHY PROCESS; ANALYSIS MCDA; SUPPORT; FRAMEWORK; CARE; SYSTEMS; MEDICINES; SELECTION; VIKOR; HTA